Bird, sweat, and tears and other stories: a collection of short stories and an exegesis - Ess, Aubrey Gabrelyn (Nanyang Technological University, 2023)
Bird, Sweat, and Tears and Other Stories is a collection of short stories examining the permutations and permanence of loss. Set in Singapore, my short story cycle contains seven stories from the mid-1950s to the mid-2020s.